"Tarred with the Same Brush": Racist and Anti-racist Constructions of Muslim Asylum Seekers in Australia. Issue 1 (2nd January 2022) - Haw, Ashleigh L.
Abstract: Despite Australia's longstanding reputation as a multicultural nation, xenophobic and integrationist ideas remain embedded within political, media and public discourse surrounding migration, especially within discussions of Muslims and asylum seekers. Existing literature indicates that within arguments that oppose refugee resettlement in Australia, Islam is routinely constructed as incompatible with Australian society. Some research, however, has highlighted resistance to these ideas, yet few studies have explored how these narratives of resistance are constructed. This paper, presents a Critical Discourse Analysis of semi-structured interviews with 24 Western Australians who discussed their perspectives concerning asylum seekers. Participants who supported restrictive asylum policies reproduced integrationist attitudes toward Muslims, however those who expressed welcoming asylum views routinely challenged these ideas. I discuss the discursive and rhetorical features of these opposing takes on Australia's asylum debate, outlining some important implications for democracy and political communication, as well as for critical race analysis and sociological scholarship.